(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study explored the role of pragmatics in English-Uzbek translation, focusing on the specific challenges and issues that arise during the translation process. Recognizing the increasing interest in pragmatics among scholars and linguists, the research emphasized its vital importance in translation practices. An analytical descriptive method was employed to meet the research goals and to pinpoint the challenges faced by translators. A questionnaire was used, divided into two sections with five items each, addressing the role of pragmatics in translation and the challenges of translating pragmatic elements from English to Uzbek. The study involved 15 Uzbek translators. The findings confirmed that pragmatics plays a crucial role in the translation process. In the first part of the questionnaire, 86% of respondents emphasized the importance of pragmatics in translation, with an average score of 2.6 out of 3. Additionally, the second part revealed that understanding pragmatics is essential for effective translation, with 83.3% of responses highlighting this need, and an average score of 2 out of 3 regarding the challenges translators face. These results underline the necessity of a strong grasp of pragmatic nuances for successful English-Uzbek translation.